2021
DOI: 10.1002/aelm.202000819
|View full text |Cite
|
Sign up to set email alerts
|

Trap Reduction through O3 Post‐Deposition Treatment of Y2O3 Thin Films Grown by Atomic Layer Deposition on Ge Substrates

Abstract: For Ge‐based metal‐oxide‐semiconductor field‐effect transistor application, high‐k Y2O3 thin films are deposited on Ge single‐crystal substrate using atomic layer deposition. The primary drawbacks of a metal‐oxide‐semiconductor capacitor with pristine Y2O3 are large hysteresis and high leakage current. Through forming gas annealing (FGA), the leakage current can be reduced by approximately three orders of magnitude, along with the reduction of interface trap density. However, there is still a large hysteresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The authors recently reported that the as-deposited amorphous Y 2 O 3 film had a highly defective property if no additional O 3 treatment was performed. Therefore, GeO diffusion appears larger in the amorphous Y 2 O 3 layer compared to the relatively stable TiO 2 layer [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors recently reported that the as-deposited amorphous Y 2 O 3 film had a highly defective property if no additional O 3 treatment was performed. Therefore, GeO diffusion appears larger in the amorphous Y 2 O 3 layer compared to the relatively stable TiO 2 layer [27].…”
Section: Resultsmentioning
confidence: 99%
“…The high ∆N st was due to ∆N st present in the Y 2 O 3 and YTO thin film layers, not due to the diffusion of Y and Ti into the Ge/GeO 2−x interface or GeO 2−x layer, as discussed later. When the thickness ratio of Y 2 O 3 :TiO 2 was 3:4, the ideal dielectric constant was calculated as ∼22.9 from the dielectric constants of Y 2 O 3 and TiO 2 of ∼15.6 and ∼35.4 in the previous reports, respectively [19,27]. The k-value of the bilayer thin film was calculated from the C-V curve of figure 6(a) as ∼17.8.…”
Section: Resultsmentioning
confidence: 99%